PRINCIPAIS INCUMPRIMENTOS NA IMPLEMENTAÇÃO DAS MEDIDAS DE AUTOPROTEÇÃO EM EDIFÍCIOS ESCOLARES - Oliveira, Rui (2022)
Self-protection measures (MAp) are a set of organized procedures created to reduce the risk of fire in buildings. It aims to preserve the human life, heritage, goods and the environment, as from the regulatory requirement since the 1st of January 2009. The history of the fire outbreaks shows the cause trend in the human behavior. Such facts prompt to acknowledge the main linked failures in the execution of the self-protection measures, nowadays and after 10 years from the regulatory requirement. The figures achieved from surveys applied to the ones responsible for scholar buildings with selfprotection measures designed, reflects que main failure as the lack of training in fire safety demanded to all the employees. In the matters of causes of those failures, it was possible to identify the lack of human resources with time to spend and with the right knowledge, as the lack of financial resources. Alongside, the ones responsible for scholar buildings without self-protection measures designed, highlight the lack of inspection pressure from ANEPC as the possible cause. The ignorance, the lack of risk perception and the responsibilities of the main actors in prevention matters and reduction of the fire risk in scholar buildings, weakens the ability to perform assertively in case a fire. The human behavior is strongly influenced by each individual’s characteristics, by the type of building and by the emergency situation itself. Training and awareness in fire safety matters are both key elements to invest towards the observance of the self-protection measures execution, as well as are an opportunity to increase the resilience of all scholar building occupants. Notably, the training for the responsible of the school building and the safety officer must be qualified. Awareness actions are highlighted to make the training given applied in a more effectively manner. The adjustment of the fines involved and its execution, along with the effort in the inspective pressure towards the observance are the path to reduce the amount of scholar buildings without self-protection measures put in place